Positive electrode material and battery

By introducing pore structures into the positive electrode material and adjusting the particle composition, the problem of insufficient fast charging performance and structural stability of the existing positive electrode materials is solved, and high capacity and excellent cycle stability are achieved to meet the needs of fast charging performance.

CN119812305APending Publication Date: 2025-04-11SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411996632.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The fast charging performance and structural stability of existing cathode materials are poor, which cannot meet the market's demand for fast charging. It is easy to generate cracks during the fast charging process, resulting in cracks during the cycle.

Method used

A positive electrode material is adopted, which has a pore structure inside it to relieve the release of compressive stress, and through the coordination of the first and second types of particles, the distribution of the pore structure and the mass content of lithium ions are adjusted to improve the overall structural stability.

Benefits of technology

It improves the structural stability and fast charging performance of the cathode material, enhances its high capacity and excellent cycle stability, and can meet the needs of fast charging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812305A_ABST
    Figure CN119812305A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a battery, the positive electrode material comprises secondary particles, and the secondary particles comprise a first type of particles and a second type of particles; in a tangent plane SEM image of the positive electrode material, the area ratio of the pore structures in the first type of particles is 0.5%-30%; the area ratio of pore structures in the second type of particles is less than 0.5%; the number of the first type of particles accounts for 50%-70% of the number of all the particles, and the number of the second type of particles accounts for 30%-50% of the number of all the particles. The positive electrode material provided by the invention has the first type of particles and the second type of particles with a proper quantity ratio, the overall structural stability of the positive electrode material can be improved, and the positive electrode material has high capacity and excellent cycling stability and can meet the requirement of fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and batteries. Background Art

[0002] With the continuous innovation and development of battery technology, the market's requirements for battery fast charging performance are constantly increasing. Ternary positive electrode materials are widely used in 3C digital products due to their superior rate performance. On the other hand, positive electrode materials are mainly used in power batteries for new energy vehicles due to their higher energy density, lower cost, and long cycle life. The existing positive electrode materials have poor fast charging performance and structural stability, and their fast charging capabilities cannot meet market demand. In addition, during the fast charging process, a significant difference in lithium ion concentration will be generated between the surface and internal areas, causing severe internal compressive stress accumulation, which is prone to cracks, and then causes the positive electrode material particles to rupture during the cycle.

[0003] Therefore, improving the structural stability of the positive electrode material so that it can meet the fast charging performance is still a technical problem that needs to be solved. Summary of the invention

[0004] The present application provides a positive electrode material and a battery. The positive electrode material has a pore structure inside, which is conducive to the release of compressive stress and can improve the structural stability of the positive electrode material so that it can meet the fast charging performance.

[0005] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a first type of particles and a second type of particles;

[0006] In the cross-sectional SEM image of the positive electrode material, the area of ​​the pore structure within the first type of particles accounts for 0.5% to 30%; the area of ​​the pore structure within the second type of particles accounts for <0.5%; based on the total number of particles in the cross-sectional SEM image of the positive electrode material, the number of the first type of particles accounts for 50% to 70%.

[0007] In some embodiments, in the cross-sectional SEM image of the first type of particles, the first type of particles include a core region and a surface region, and in the circumscribed circle of the outline of a single first type of particle, the region within a radius of 2 μm radially outward from the center of the circumscribed circle is the core region, and the region other than the core region is the surface region;

[0008] The number of the pore structures distributed in the core region accounts for R, and R≥70%.

[0009] In some embodiments, the mass content of lithium ions in the core region is m Li内 The mass content of lithium ions in the surface area is m Li外 , 0.55≤m Li内 / m Li外 ≤0.85.

[0010] In some embodiments, in the cross-sectional SEM image of the first type of particles, the maximum distance between the edges of any two adjacent pore structures is ≤2.5 μm.

[0011] In some embodiments, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.30, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and M includes at least one of Mo, Ti, Zr, Sb, Y, W, Al, Sr, Ba, Ca and B.

[0012] In some embodiments, the volume distribution particle size D50 of the positive electrode material is 7 μm to 12 μm.

[0013] In some embodiments, the compaction density of the positive electrode material is 2.8 g / cm 3 ~3.5g / cm 3 .

[0014] In some embodiments, the lithium-nickel mixing ratio of the positive electrode material is 2% to 6%.

[0015] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is The positive electrode material has a c-axis unit cell parameter c, an a-axis unit cell parameter a, And c / a>4.94.

[0016] In a second aspect, the present application provides a battery, comprising the above-mentioned positive electrode material.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects:

[0018] In the present application, the number of the first type of particles in all the particles accounts for 30% to 50%, and the number of the second type of particles in all the particles accounts for 50% to 70%. The two types of particles are matched with each other. The first type of particles with an appropriate number and proportion can alleviate the expansion stress generated during the lithium deintercalation process of the lattice due to the presence of the pore structure, and are beneficial to the release of the expansion stress in the lattice during the charging and discharging process (especially the rapid charging and discharging process). With an appropriate amount of the second type of particles, the overall structural stability of the positive electrode material can be improved. The positive electrode material has high capacity and excellent cycle stability, and can meet the fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0020] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.

[0021] Figure 2 This is a SEM cross-sectional view of the positive electrode material prepared in Example 1 of the present invention.

[0022] Figure 3 This is a SEM cross-sectional view of the positive electrode material prepared in Example 12 of the present invention.

[0023] Figure 4 This is a SEM cross-sectional view of the positive electrode material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0025] It should be clear that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0027] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0028] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a first type of particles and a second type of particles;

[0029] In the cross-sectional SEM image of the positive electrode material, the area of ​​the pore structure within the first type of particles accounts for 0.5% to 30%; the area of ​​the pore structure within the second type of particles accounts for <0.5%; based on the total number of particles in the cross-sectional SEM image of the positive electrode material, the number of the first type of particles in all particles accounts for 50% to 70%.

[0030] In the positive electrode material provided by the present application, the area of ​​the pore structure in the first type of particles in the positive electrode material accounts for 0.5% to 30%. The presence of an appropriate amount of pore structure can shorten the diffusion distance of lithium ions, accelerate the transmission of lithium ions, increase the first discharge capacity and the first coulomb efficiency, and improve the rate performance of the positive electrode material; in addition, the area of ​​the pore structure of the second type of particles accounts for less than 0.5%. The second type of particles has higher structural stability, can reduce the particle breakage during the rolling process of the electrode sheet, and thus reduce the loss of active ions due to the continuous formation of broken surfaces, reduce the irreversible loss of capacity, and comprehensively improve the compressive strength and cycle performance of the positive electrode material. In the present application, the first type of particles accounts for 30% to 50% of all the particles, and the second type of particles accounts for 50% to 70% of all the particles. The two types of particles are matched with each other. During the lithium deintercalation process, the existence of the pore structure can alleviate the expansion stress generated during the lattice lithium deintercalation process. During the charging and discharging process (especially the rapid charging and discharging process), the first type of particles with an appropriate number and proportion are beneficial to the release of the expansion stress in the lattice. With an appropriate amount of the second type of particles, the overall structural stability of the positive electrode material can be improved. The positive electrode material has high capacity and excellent cycle stability, and can meet the fast charging performance.

[0031] It should be noted that the pore structure in the present application refers to a pore structure having a maximum length and width of more than 200 nm in a cross-sectional SEM image.

[0032] In this application, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.30, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and M is a metal element.

[0033] The specific value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the specific value of a can be 0.5, 0.51, 0.52, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9 or 0.98, and the value of b can be 0.01, 0.05, 0.09, 0.1, 0.11, 0.1 The value of c can be 0.1, 0.2, 0.25, 0.30, 031, 0.32, 0.33, 0.34 or 0.35, and the value of d can be 0, 0.001, 0.005, 0.006, 0.008, 0.009, 0.01, 0.02, 0.03, 0.05, 0.07 or 0.1, etc., and is not limited here.

[0034] In some embodiments, the M element includes at least one of Mo, Ti, Zr, Sb, Y, W, Al, Sr, Ba, Ca and B. It can be understood that an appropriate amount of M element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing.

[0035] The positive electrode material includes secondary particles formed by agglomeration of multiple primary particles. The secondary particles are spherical or quasi-spherical in structure. The cross section of the secondary particles is roughly circular. In the cross section of the secondary particles, the straight line direction along the radius or the straight line direction along the diameter is the radial direction.

[0036] In the present application, in the cross-sectional SEM image of the first type of particles, the first type of particles have a pore structure, and the area of ​​the pore structure in the first type of particles accounts for 0.5% to 30%, specifically 0.5%, 1%, 2%, 5%, 10%, 15%, 20%, 25%, 30%, etc., and of course other values ​​within the above range, which are not limited here. Preferably, the area of ​​the pore structure in the first type of particles accounts for 10%-30%.

[0037] In some embodiments, in the cross-sectional SEM image of the second type of particles, the pore structure area of ​​the second type of particles is less than 0.5%, specifically 0.49%, 0.4%, 0.3%, 0.2%, 0.1%, 0.05%, 0.01%, 0, etc., and of course other values ​​within the above range, which are not limited here. It can be understood that when the pore structure area is 0, the secondary particle is a solid structure.

[0038] In some embodiments, in the cross-sectional SEM image of the positive electrode material, the number of the first type of particles in all particles accounts for 50% to 70%, specifically 50%, 55%, 57%, 60%, 62%, 65%, 67%, 70%, etc., and of course other values ​​within the above range, which are not limited here. When the number of the first type of particles accounts for too small a proportion, the diffusion distance of lithium ions inside the positive electrode material particles increases, and the transmission efficiency of lithium ions decreases, which is not conducive to improving the rate performance of the positive electrode material. When the number of the first type of particles accounts for too much, the structural stability of the positive electrode material decreases, the particle crushing phenomenon during the pole piece rolling process intensifies, and the capacity and first coulomb efficiency of the positive electrode material decrease. The present application controls the number of the first type of particles in all particles to be within the above range, which is conducive to improving the lithium ion transmission efficiency. At the same time, due to the presence of the pore structure, the expansion stress generated during the lattice lithium deintercalation process can be alleviated, thereby improving the structural stability and fast charging performance of the positive electrode material.

[0039] In some embodiments, in the cross-sectional SEM image of the first type of particles, the first type of particles include a core region and a surface region, and in the circumscribed circle of the outline of a single first type of particle, the area within a radius of 2 μm radially outward from the center of the circumscribed circle is the core region, and the area other than the core region is the surface region.

[0040] In some embodiments, in the cross-sectional SEM image of the first type of particles, the number of pore structures distributed in the core region accounts for ≥70%, which can be 70%, 72%, 75%, 80%, 85%, 89%, 90%, 95%, 96%, 100%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. When the number of pore structures distributed in the core region is controlled within the above range, it can be seen that most of the pore structures are located in the core region, and the core region of the particle has a partially hollow pore structure, which can effectively alleviate the irreversible transformation of the layered phase structure into the rock salt phase structure and buffer the lattice expansion stress under high voltage; and the surface area of ​​the particle is relatively dense, and its structural stability is better. On the basis of the existence of the internal pore structure, it is beneficial to suppress the volume change caused by the internal stress and reduce the particle rupture, thereby improving the cycle stability of the positive electrode material.

[0041] In some embodiments, the mass content of lithium ions in the core region is m Li内 The mass content of lithium ions in the surface area is m Li外 , 0.55≤m Li内 / m Li外 ≤0.85m Li内 / m Li外Specifically, it can be 0.55, 0.58, 0.6, 0.62, 0.65, 0.68, 0.7, 0.73, 0.75, 0.78, 0.80, 0.82 or 0.85, etc. Of course, it can also be other values ​​within the above range, which are not limited here. It can be understood that the lithium ion content of the core region is lower than that of the surface region. This can ensure that the stress generated in the core region during lithium insertion and extraction is reduced, and the cracks caused by lattice contraction and expansion are reduced. In addition, the core region has a pore structure, which can help disperse and buffer the stress and is beneficial to the cycle stability of the core region. The lithium ion content in the surface region is relatively high. During rapid charging and discharging, the stress of lattice contraction and expansion in the surface region can be better dispersed. This application will be m Li内 / m Li外 By controlling within the above range, the structural stability of the positive electrode material can be improved and the fast charging performance can be met.

[0042] In some embodiments, in the cross-sectional SEM image of the first type of particles, the maximum distance between the edges of any two adjacent pore structures is ≤2.5μm, which can be 2.5μm, 2μm, 1.5μm, 1.2μm, 1μm, 0.8μm or 0.5μm, etc. Of course, it can also be other values ​​within the above range, which are not limited here. In the present application, in the cross-sectional SEM image of the first type of particles, the maximum distance between the edges of any two adjacent pore structures is ≤2.5μm, and the pore structures are mainly concentrated in the inner core area of ​​the second type of area, which can leave sufficient buffer space for lattice contraction and expansion under high voltage, effectively release stress, and alleviate anisotropic lattice contraction under high voltage, thereby reducing the generation of cracks; and it can also provide more lithium ion migration channels, accelerate lithium ion transmission efficiency, and enable the positive electrode material to meet fast charging performance. In the present application, the distance between the edges of two adjacent pore structures refers to the minimum distance between the edges of two adjacent pores in two adjacent pore structures. It should be noted that, in the present application, in the definition of two adjacent hole structures, the two hole edges with the smallest distance are defined as two close hole edges, and the two hole edges with the largest distance are defined as two far away hole edges.

[0043] In some embodiments, the secondary particles have a coating layer on their surfaces, and the coating layer includes a lithium composite oxide containing element M. It can be understood that the coating layer on the secondary particles can reduce direct contact with the electrolyte, reduce the occurrence of side reactions, and thus improve the cycle stability of the positive electrode material.

[0044] In some embodiments, the lithium-nickel mixing rate of the positive electrode material is 2% to 6%, specifically 2.0%, 2.4%, 2.8%, 3.0%, 3.2%, 3.4%, 3.8%, 4%, 4.5%, 4.8%, 5%, 5.4% or 6%, etc., of course, it can also be other values ​​within the above range, which are not limited here. It can be understood that when the lithium-nickel mixing rate of the positive electrode material is too high, some nickel ions will occupy the position of the original lithium ions, destroy the orderliness of the crystal structure, cause lattice distortion, reduce the number of lithium ions to be deintercalated, and reduce the capacity. The present application controls the lithium-nickel mixing rate within the above range, which can reduce lattice distortion, reduce the local stress aggravation caused by the lithium ion deintercalation process, improve the particle structure stability of the positive electrode material, reduce particle rupture, improve the reversible discharge capacity of the positive electrode material, and improve the cycle life of the battery.

[0045] In some embodiments, the volume distribution particle size D50 of the positive electrode material is 7 μm to 12 μm, specifically 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or a number between any two values ​​thereof, which is not limited here. Since the median particle size of the positive electrode material is within the above range, the particles within this size range have better electrochemical properties, higher discharge capacity and excellent rate performance.

[0046] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 0.9≤(D 90 -D 10 ) / D 50 ≤1.6, specifically 0.9, 1.05, 1.08, 1.1, 1.15, 1.18, 1.2, 1.22, 1.25, 1.26, 1.3, 1.35, 1.4, 1.5 or 1.6, etc., and of course, other values ​​within the above range are also possible, which are not limited here. In the present application, by controlling the particle size distribution width of the positive electrode material within the above range, particles of different sizes can be stacked more closely, so that the compaction density of the positive electrode sheet is improved and the energy density is higher.

[0047] In some embodiments, the compacted density of the positive electrode material is 2.8 g / cm 3 ~3.5g / cm 3 , specifically 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 , 3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3、3.45g / cm 3 or 3.5g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here.

[0048] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume of the positive electrode material is V can be Of course, it can also be other values ​​within the above range and is not limited here.

[0049] The unit cell volume of the positive electrode material in the present application is within the above range, the distance between transition metal atoms is shorter, and the bond energy between transition metal atoms is stronger, so that the expansion of cracks on the particle surface and extending to the interior of the particle requires overcoming a higher potential barrier, thereby inhibiting the diffusion of cracks and improving cycle stability. Keeping the unit cell volume within an appropriate range is beneficial to maintaining the stability of the crystal structure and reducing volume changes during charging and discharging.

[0050] In some embodiments, the cathode material is subjected to XRD measurement using Cu-Kα rays, and the cathode material unit cell parameter ratio c / a>4.94. c / a can be 4.941, 4.945, 4.948, 4.95, 4.96, 4.98, 4.99, etc., which is not limited here.

[0051] In some embodiments, the unit cell parameter of the a-axis of the positive electrode material is Specifically it can be Of course, it can also be other values ​​within the above range and is not limited here.

[0052] In some embodiments, the c-axis unit cell parameter of the positive electrode material is Specifically it can be Of course, it can also be other values ​​within the above range and is not limited here.

[0053] In the present application, the unit cell parameter ratio c / a of the positive electrode material is within the above range, which indicates that the crystal structure of the positive electrode material is stable, the internal doping of the positive electrode material is uniform, and the internal defects of the positive electrode material crystal can be reduced, which is beneficial to the improvement of the capacity of the positive electrode material.

[0054] In a second aspect, the present application provides a method for preparing a positive electrode material, the method for preparing a positive electrode material comprising the following steps:

[0055] S10, preparing a mixed salt solution of nickel, manganese and N elements according to a preset ratio, and adding a pH adjuster to carry out a coprecipitation reaction, wherein the coprecipitation reaction includes a first stage and a second stage, wherein the stirring rate of the first stage is 200 rpm to 300 rpm, and the pH value is 10.5 to 11.6, and the stirring rate of the second stage is 300 rpm to 700 rpm, and the pH value is 11.0 to 12.0, and a precursor is obtained by solid-liquid separation.

[0056] S20, subjecting the mixture of the precursor, the lithium source and the dopant to a sintering treatment to obtain a sintering product. The sintering treatment includes a first sintering stage and a second sintering stage. The temperature of the first sintering stage is 400°C to 650°C, and the temperature of the second sintering stage is 750°C to 900°C.

[0057] S30, mixing the primary sintered product with the coating agent, and then performing a secondary sintering process to obtain a positive electrode material.

[0058] The preparation method of the positive electrode material provided by the present application first controls the two stages of the coprecipitation reaction process. Since the stirring rate of the mixed salt solution in the first stage is low and the stirring rate in the second stage is high, a precursor with an internal pore structure can be formed. The existence of the pore structure is conducive to the full release of the stress accumulated by the lattice phase change, reducing the particle rupture of the positive electrode material particles during the cycle process, and improving the cycle stability of the positive electrode material. Then, the precursor is sintered with a lithium source and a dopant. The sintering process includes a first sintering stage and a second sintering stage. Different sintering temperatures cause a temperature difference between the inner and outer layers of the precursor particles. The outer layer temperature is high, the primary particles grow faster and larger in size, and the primary particles are closely arranged; the inner layer temperature is low, the primary particles grow slowly, and the size of the primary particles is smaller than that of the outer layer, and the internal voids cannot be filled, thereby forming a sintered product with an internal pore structure. Finally, the matrix material and the coating agent are mixed and sintered for a second time. During the mixing process, at least part of the coating agent can coat the primary particles in the surface area, so that a coating layer is formed on the outer surfaces of the primary particles in the surface area and the secondary particles, thereby coating the surface of the positive electrode material particles and the primary particles inside the positive electrode material, achieving double protection and improving cycle stability.

[0059] The preparation method of the present application is described in detail below with reference to the examples:

[0060] S10, preparing a mixed salt solution of nickel, manganese and N elements according to a preset ratio, and adding a pH adjuster to carry out a coprecipitation reaction, wherein the coprecipitation reaction includes a first stage and a second stage, wherein the stirring rate of the first stage is 200rpm-300rpm, the pH value is 10.5-11.6, the stirring rate of the second stage is 300rpm-700rpm, the pH value is 11.0-12.0, and a precursor is obtained by solid-liquid separation; the N element includes Mn element and / or Al.

[0061] In some embodiments, the stoichiometric ratio range between nickel, cobalt, and N elements meets the following conditions: 0.5≤Ni≤0.98, 0<Co≤0.2, 0<Mn≤0.35; the molar ratio of Ni:Co:Mn can specifically be 0.60:0.10:0.30, 0.67:0.05:0.28 or 0.90:0.05:0.05, etc.

[0062] In some embodiments, the salt solution is at least one of nitrate, hydrochloride, sulfate, carbonate, oxalate, and acetate. For example, the nickel salt solution can be at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate. Of course, nickel, N element, and cobalt can also be metal element raw materials or recycled materials of ternary positive electrode materials, which are not limited here.

[0063] In some embodiments, a compound containing element N is further added to the salt solution according to a target doping ratio, which may specifically be a nitrate containing element N, a hydrochloride containing element N, an acid containing element N, etc., which is not limited here.

[0064] In some embodiments, the coprecipitation reaction includes a first stage and a second stage, wherein the stirring rate of the first stage is 200 rpm to 300 rpm, and the pH value is 10.5 to 11.6. The stirring rate of the first stage can be 200 rpm, 220 rpm, 230 rpm, 250 rpm, 260 rpm, 280 rpm, 300 rpm, or any value therebetween, without limitation herein. The pH value can be 10.5, 10.8, 10.9, 10.0, 11.2, 11.4, 1.6, or any value therebetween, without limitation herein.

[0065] In some embodiments, the stirring rate of the second stage is 300 rpm to 700 rpm, and the pH value is 11.0 to 12.0. The stirring rate of the second stage can be 300 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm or any value therebetween, which is not limited herein. The pH value can be 11.0, 11.1, 11.3, 11.5, 11.8, 11.9, 12.0 or any value therebetween, which is not limited herein.

[0066] In the present application, the stirring rates of the two stages of the coprecipitation reaction are controlled to be different, so that the interior of the precursor presents a loose structure and the outer layer of the precursor is more compact, which is conducive to the formation of a precursor with internal pores.

[0067] In some embodiments, the chemical formula of the cathode material precursor is Ni x Co y M z (OH)2, wherein x+y+z=1, 0.5≤x, y+z≤0.5, and M is Mn and / or Al.

[0068] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium oxide, lithium nitrate, lithium acetate, lithium sulfate, and lithium oxalate.

[0069] In some embodiments, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metals in the positive electrode material precursor is controlled to be (0.99-1.3): 1. Exemplarily, the molar amount ratio of the total molar amount of Ni, Co and M in the positive electrode material precursor to the molar amount of Li is 1: (0.99-1.3); specifically, it can be 0.99:1, 1.0:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1 or 1.3:1, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0070] It can be understood that controlling the amount of lithium source added can ensure that the interior of the primary sintered product has a loose porous structure, and the shell region of the primary sintered product has a compact and dense structure. When too little lithium source is added, the inner core radius of the sintered matrix material is too small, and it is difficult to provide strong structural support for the secondary particles. The shell layer on the surface of the inner core is more likely to collapse or break, and the structural stability decreases. When the amount of lithium source added is too much, the pore structure rate of the shell layer of the matrix material decreases, resulting in a reduction in lithium ion transmission channels and a decrease in the first discharge capacity of the positive electrode material. Preferably, the ratio of the molar amount of Li in the lithium source to the total molar amount of the transition metal in the positive electrode material precursor is controlled to be (0.99~1.1):1.

[0071] In some embodiments, the dopant includes at least one of an oxide containing the M1 element, a hydroxide containing the M1 element, an oxyhydroxide containing the M1 element, and an oxide of a non-metallic element.

[0072] In some embodiments, the M1 element includes at least one of Mo, Ti, Zr, Sb, Y, W, Al, Sr, Ba, Ca, and B.

[0073] In some embodiments, the mixture of the precursor, the lithium source and the dopant may be mixed by dry grinding, ball milling, etc., which is not limited here, as long as the components are mixed evenly.

[0074] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.

[0075] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, which may be air or a mixed gas of air and oxygen.

[0076] In some embodiments, the volume content of oxygen in the oxygen-containing atmosphere is greater than 95%.

[0077] In some embodiments, the primary sintering process includes a first sintering stage and a second sintering stage, the temperature of the first sintering stage is 400°C to 650°C, and the temperature of the second sintering stage is 750°C to 900°C.

[0078] A sintering process can be repeated many times, so that there is a certain temperature difference between the inner and outer layers of the precursor. Since the primary particles in the outer layer of the precursor are large and the temperature is high, the primary particles grow quickly and can form large-sized primary particles. Finally, the large-sized primary particles in the outer layer are arranged as a whole, thus forming a dense surface area structure morphology. The primary particles in the inner core area are relatively small and the temperature is relatively low. They grow slowly and the size of the primary particles is relatively small. It is difficult for the primary particles to completely fill the internal gaps, and finally the inner core area has a porous structure.

[0079] The precursor prepared by the present application and the above-mentioned primary sintering process can promote the growth and fusion of the primary particles on the surface, forming a dense structure on the surface. The internal temperature of the precursor is low, and the growth rate of the primary particles is lower than that of the surface, which helps to form a partially hollow pore structure in the internal area.

[0080] Specifically, the temperature of the first heating stage can be 400°C, 430°C, 450°C, 500°C, 520°C, 540°C, 580°C, 600°C, 630°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] The temperature of the second heating stage can be 750°C, 770°C, 780°C, 800°C, 820°C, 830°C, 840°C, 850°C, 880°C or 900°C, etc., but is not limited to the listed values. Other values ​​not listed in this numerical range are also applicable. When the temperature is too low, the particle size of the primary particles decreases, the pore structure rate in the surface area increases, and the density of the surface area decreases, resulting in excessive contact area between the positive electrode material and the electrolyte, increased side reactions, and decreased structural stability of the positive electrode material. When the temperature is too high, the particle size of the primary particles increases, the density of the surface area of ​​the secondary particles is too large, the wettability of the electrolyte decreases, and the initial charge and discharge capacity of the positive electrode material decreases.

[0082] In some embodiments, the second heating stage includes multiple heating sections, for example, the temperature may be rapidly increased to 800° C. in the second section at a heating rate of 15° C. / min and kept at that temperature for 2 hours, then increased to 850° C. at a heating rate of 15° C. / min and kept at that temperature for 2 hours, and then increased to 900° C. at a heating rate of 15° C. / min and kept at that temperature for 2 hours.

[0083] In some embodiments, the time for a sintering treatment is 9 h to 15 h, specifically 9 h, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] Step S30, mixing the primary sintering product with the first coating agent, and then performing a secondary sintering process to obtain a positive electrode material.

[0085] The mixing method is the same as that in step S20 and will not be described again.

[0086] In some embodiments, the first coating agent includes at least one of an oxide containing the M1 element, a hydroxide containing the M1 element, an oxyhydroxide containing the M1 element, and an oxide of a non-metallic element.

[0087] In some embodiments, the oxide containing the M1 element includes at least one of magnesium oxide, yttrium oxide, niobium oxide, molybdenum oxide, titanium oxide, scandium oxide, cerium oxide, aluminum oxide, cobalt oxide, manganese oxide, boron oxide, tantalum oxide, and strontium oxide.

[0088] In some embodiments, the hydroxide containing the M1 element includes at least one of magnesium hydroxide, yttrium hydroxide, niobium hydroxide, molybdenum hydroxide, titanium hydroxide, scandium hydroxide, cerium hydroxide, aluminum hydroxide, cobalt hydroxide, manganese hydroxide, boron hydroxide, tantalum hydroxide, and strontium hydroxide.

[0089] It can be understood that adding a coating agent and performing a secondary sintering treatment can form a lithium metal composite oxide with high lithium ion conductivity at the grain boundaries between primary particles in the surface area, reduce the grain boundary transmission impedance, and help improve the rate performance of the positive electrode material.

[0090] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere; the oxygen-containing atmosphere may be air or a mixed gas of oxygen.

[0091] In some embodiments, the temperature of the secondary sintering treatment is 400°C to 700°C; specifically, it can be 400°C, 450°C, 480°C, 500°C, 520°C, 550°C, 600°C, 650°C, 680°C or 700°C, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the temperature of the secondary sintering treatment is 550°C to 700°C.

[0092] In some embodiments, the secondary sintering treatment time is 5 h to 15 h; specifically, it can be 5 h, 6 h, 8 h, 10 h, 12 h, 14 h or 15 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0093] In some embodiments, based on the mass of the primary sintered product as 100%, the amount of the first coating agent added is 0.1% to 1%, specifically 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8% or 1%, etc., which are not limited here. Preferably, based on the mass of the primary sintered product as 100%, the amount of the first coating agent added is 0.1% to 0.3%.

[0094] During the secondary sintering process, part of the metal oxide or metal hydroxide will react with the residual alkali on the surface of the primary sintering product to generate lithium metal oxoate, which reduces some of the residual alkali on the surface and improves the rate performance of the positive electrode material. The remaining coating agent will form a lithium metal composite oxide to coat the surface of the secondary particles, improve the surface structure of the positive electrode material, and inhibit the side reaction between the positive electrode material and the electrolyte.

[0095] In some embodiments, the method further comprises: solid-phase mixing the secondary sintering product with the second coating agent and performing a third sintering process to obtain a positive electrode material.

[0096] In some embodiments, the second coating agent includes at least one of an oxide containing an M2 element, a salt containing an M2 element, and an acid containing an M2 element, wherein the M2 element includes at least one of W, Mo, Li, and B.

[0097] In some embodiments, the second coating agent includes at least one of boric acid, boron oxide, boron fluoride, lithium oxalate, tungsten oxide, tungstic acid, lithium tungstate, molybdenum oxide, molybdic acid, and lithium molybdate.

[0098] In some embodiments, based on the mass of the secondary sintered product as 100%, the amount of the second coating agent added is 0.1% to 1%, specifically 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8% or 1%, etc., which are not limited here. Preferably, based on the mass of the secondary sintered product as 100%, the amount of the second coating agent added is 0.1% to 0.5%.

[0099] In some embodiments, the tertiary sintering process is performed in an oxygen-containing atmosphere; the oxygen-containing atmosphere may be air or a mixed gas of oxygen.

[0100] In some embodiments, the temperature of the three sintering treatments is 250°C to 350°C; specifically, it can be 250°C, 280°C, 300°C, 320°C, 330°C or 350°C, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the temperature of the three sintering treatments is 250°C to 350°C.

[0101] In some embodiments, the time for the three sintering treatments is 5 h to 15 h; specifically, it can be 5 h, 6 h, 8 h, 10 h, 12 h, 14 h or 15 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0102] By controlling the temperature and time of the tertiary sintering treatment and the type and amount of the second coating agent, it can be ensured that the second coating agent can form a dense coating layer on the surface of the secondary particles of the positive electrode material, thereby providing dual protection for the secondary particles and the primary particles in the surface area, thereby improving the structural stability of the positive electrode material and further improving the cycle stability.

[0103] In some embodiments, the preparation method further comprises cooling, shaping and screening the product after the third sintering. The shaping comprises at least one of crushing, grinding, ball milling or gas crushing.

[0104] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0105] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0106] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0107] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.

[0108] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.

[0109] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0110] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0111] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0112] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.

[0113] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.

[0114] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0115] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0116] Example 1

[0117] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.5, the stirring speed was 340 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0118] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then increase the temperature to the second heating stage at 10℃ / min, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0119] (3) 3.6 g of Al2O3, 2.8 g of TiO2 and 1000 g of the matrix material were weighed, ball-milled and mixed, and then subjected to secondary sintering at 600°C. The sintered product was crushed and sieved through 325 mesh to obtain a secondary sintered product.

[0120] (4) Weigh 4.5 g of boric acid and 1000 g of the secondary sintered product, mix them by ball milling, and then keep them at 310° C. for 5 h. After sintering, crush and sieve through 325 mesh to obtain a positive electrode material.

[0121] Figure 2 This is a SEM cross-sectional view of the positive electrode material prepared in Example 1 of the present invention. Figure 2 As shown, the number of secondary particles with hollow structures in the cross-sectional view of the positive electrode material accounts for 51.3%. The chemical formula of the positive electrode material prepared in Example 1 is shown in Table 2, wherein the doping elements include W, Ti, Sr and Al. Since the amount of the doping elements is difficult to accurately determine, it is not reflected in the chemical formula. The chemical formulas in other embodiments are the same as those in Example 1.

[0122] Example 2

[0123] The difference between this embodiment and embodiment 1 is that

[0124] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased and finally stabilized to pH = 11.8, the stirring speed was 380 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0125] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 15℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0126] The other operations are the same as those in Example 1.

[0127] Example 3

[0128] The difference between this embodiment and embodiment 1 is that

[0129] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased and finally stabilized to pH = 12.1, the stirring speed was 550 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0130] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 20℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0131] The other operations are the same as those in Example 1.

[0132] Example 4

[0133] The difference between this embodiment and embodiment 1 is that

[0134] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.3 μm, the pH and stirring rate were gradually increased and finally stabilized to pH = 11.5, the stirring speed was 350 rpm, and after the particle size reached 2.3 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 6 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0135] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 15℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0136] The other operations are the same as those in Example 1.

[0137] Example 5

[0138] The difference between this embodiment and embodiment 1 is that

[0139] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.3 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.8, the stirring speed was 400 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 6 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0140] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 20℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0141] The other operations are the same as those in Example 1.

[0142] Example 6

[0143] The difference between this embodiment and embodiment 1 is that

[0144] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 3.0 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.2, the stirring speed was 520 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 6 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0145] (2) Weigh 1000g of precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 25℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0146] The other operations are the same as those in Example 1.

[0147] Example 7

[0148] The difference between this embodiment and embodiment 1 is that

[0149] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.5 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.2, the stirring speed was 320 rpm, and after the particle size reached 2.4 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 8 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0150] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then increase the temperature to the second heating stage at 10℃ / min, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0151] The other operations are the same as those in Example 1.

[0152] Example 8

[0153] The difference between this embodiment and embodiment 1 is that

[0154] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.5 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.5, the stirring speed was 390 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 8 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0155] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 15℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0156] The other operations are the same as those in Example 1.

[0157] Example 9

[0158] The difference between this embodiment and embodiment 1 is that

[0159] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 1.5 μm, the pH and stirring rate were gradually increased and finally stabilized to pH = 12.2, the stirring speed was 550 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 8 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0160] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 20℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0161] The other operations are the same as those in Example 1.

[0162] Example 10

[0163] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 7:1:2 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH=11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH=11.5, the stirring speed was 340 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.7 Co 0.1 Mn 0.2 (OH)2.

[0164] (2) Weigh 1000g of the above precursor Ni 0.7 Co 0.1 Mn 0.2(OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 5℃ / min to the second heating stage, the second heating stage includes first heating to 800℃ in the first stage and keeping it for 2h, then heating to 850℃ in the second stage and keeping it for 2h, and finally heating to 900℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0165] (3) 3.6 g of Al2O3, 2.8 g of TiO2 and 1000 g of the matrix material were weighed, ball-milled and mixed, and then subjected to secondary sintering at 600°C. The sintered product was crushed and sieved through 325 mesh to obtain a secondary sintered product.

[0166] (4) Weigh 4.5 g of boric acid and 1000 g of the secondary sintered product, mix them by ball milling, and then keep them at 310° C. for 5 h. After sintering, crush and sieve through 325 mesh to obtain a positive electrode material.

[0167] Embodiment 11

[0168] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 0.98:0.01:0.01 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH=11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH=11.5, the stirring speed was 340 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.98 Co 0.01 Mn 0.01 (OH)2.

[0169] (2) Weigh 1000g of the above precursor Ni 0.98 Co 0.01 Mn 0.01(OH)2, weigh LiOH·H2O with a purity of 99% according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, and 0.3g Al(OH)3, ball-mill the raw materials and mix them evenly, and then perform a sintering treatment in an oxygen atmosphere. The first sintering treatment includes a first heating stage and a second heating stage. The temperature of the first heating stage is increased at 10℃ / min to 560℃, and the temperature is kept for 4h. Then the temperature is increased at 10℃ / min to the second heating stage. The second heating stage includes first heating to 610℃ in the first stage and keeping it for 2h, then heating to 670℃ in the second stage and keeping it for 2h, and finally heating to 730℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0170] (3) 3.6 g of Al2O3, 2.8 g of TiO2 and 1000 g of the matrix material were weighed, ball-milled and mixed, and then subjected to secondary sintering at 600°C. The sintered product was crushed and sieved through 325 mesh to obtain a secondary sintered product.

[0171] (4) Weigh 4.5 g of boric acid and 1000 g of the secondary sintered product, mix them by ball milling, and then keep them at 310° C. for 5 h. After sintering, crush and sieve through 325 mesh to obtain a positive electrode material.

[0172] Example 12

[0173] The difference between this embodiment and embodiment 1 is that

[0174] (1) 3 mol / L nickel sulfate solution, cobalt sulfate solution, and aluminum sulfate solution were prepared according to the molar ratio of Ni, Co, and Al being 8:1:1 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH=11, and the stirring rate was 280 rpm. After the particle size grew to 1.2 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH=11.5, the stirring rate was 340 rpm, and after the particle size reached 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the aluminum sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.8 Co 0.1 Al 0.1 (OH)2.

[0175] (2) Weigh 1000g of the above precursor Ni 0.8 Co 0.1 Al 0.1(OH)2, weigh LiOH·H2O with a purity of 99% according to the ratio of Li / (Ni+Co+Al)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, and 0.3g Al(OH)3, ball-mill the raw materials to mix them evenly, and then perform a sintering treatment in an oxygen atmosphere. The first sintering treatment includes a first heating stage and a second heating stage. The temperature of the first heating stage is increased at 10℃ / min to 500℃, and the temperature is kept for 4h. Then the temperature is increased at 15℃ / min to the second heating stage. The second heating stage includes first heating to 700℃ in the first stage and keeping it for 2h, then heating to 750℃ in the second stage and keeping it for 2h, and finally heating to 800℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0176] The other operations are the same as those in Example 1.

[0177] Figure 3 This is a SEM cross-sectional view of the positive electrode material prepared in Example 12 of the present invention. The number of first-type particles in the cross-sectional view of the positive electrode material accounts for 67.3%, and all the pore structures are distributed in the circumscribed circle of the first-type particles.

[0178] Comparative Example 1

[0179] The difference between this embodiment and embodiment 1 is that

[0180] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. The coprecipitation reaction was stopped after the particle size grew to 2.2 μm, and the precursor Ni was filtered and dried to obtain 0.5 Co 0.2 Mn 0.3 (OH)2.

[0181] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials to mix them evenly, and then perform a sintering treatment in an oxygen atmosphere at a sintering temperature of 850℃ for 6h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0182] The other operations are the same as those in Example 1.

[0183] Figure 4 This is a SEM cross-sectional view of the positive electrode material prepared in Comparative Example 1 of the present invention. There is no pore structure in the cross-sectional view of the positive electrode material.

[0184] Comparative Example 2

[0185] The difference between this embodiment and embodiment 1 is that

[0186] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution, and ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 280 rpm. After the particle size grew to 2.1 μm, the pH and stirring rate were gradually increased, and finally stabilized to pH = 11.5, the stirring speed was 390 rpm, and after the particle size grew to 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 5 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0187] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, weigh LiOH·H2O with a purity of 99% according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, and 0.3g Al(OH)3, ball-mill the raw materials and mix them evenly, and then perform a sintering treatment in an oxygen atmosphere. The first sintering treatment includes a first heating stage and a second heating stage. The temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 2℃ / min to the second heating stage. The second heating stage includes first heating to 700℃ in the first stage and keeping it for 2h, then heating to 750℃ in the second stage and keeping it for 2h, and finally heating to 800℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0188] The other operations are the same as those in Example 1.

[0189] Comparative Example 3

[0190] The difference between this embodiment and embodiment 1 is that

[0191] (1) A 3 mol / L nickel sulfate solution, a cobalt sulfate solution, and a manganese sulfate solution were prepared according to a molar ratio of Ni, Co, and Mn of 5:2:3 to obtain a mixed salt solution. Ammonia water and sodium hydroxide solution were added to the mixed salt solution for coprecipitation reaction. The reaction temperature was controlled at 55°C, pH = 11, and the stirring rate was 200 rpm. After the particle size grew to 1.8 μm, the pH and stirring rate were gradually increased and finally stabilized to pH = 12.2, the stirring rate was 600 rpm, and after the particle size grew to 2.2 μm, the concentrations of the nickel sulfate solution, the cobalt sulfate solution, and the manganese sulfate solution were adjusted to 5 mol / L, and the flow rates of ammonia water and sodium hydroxide solution were adjusted to complete the coprecipitation reaction. After the coprecipitation reaction for 4 hours, the precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2.

[0192] (2) Weigh 1000g of the above precursor Ni 0.5 Co 0.2 Mn 0.3 (OH)2, weigh 99% pure LiOH·H2O according to the ratio of Li / (Ni+Co+Mn)=1.05, then add 1.2g WO3 and 0.4g Ti(OH)2, 0.4g Sr(OH)2, 0.3g Al(OH)3, ball mill the raw materials and mix them evenly, then perform a sintering treatment in an oxygen atmosphere, the first sintering treatment includes the first heating stage and the second heating stage, the temperature of the first heating stage is increased at 10℃ / min to 550℃, and the temperature is kept for 4h. Then the temperature is increased at 25℃ / min to the second heating stage, the second heating stage includes first heating to 820℃ in the first stage and keeping it for 2h, then heating to 870℃ in the second stage and keeping it for 2h, and finally heating to 950℃ in the third stage and keeping it for 2h. After crushing and 325 mesh screening, the matrix material can be obtained.

[0193] The other operations are the same as those in Example 1.

[0194] Test method:

[0195] (1) Test of metal elements in positive electrode materials:

[0196] Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as the metal element M by ICP. The determination is carried out using Agilent 5110ICP-OES detection equipment.

[0197] (2) Scanning electron microscopy test of the cross section of the positive electrode material:

[0198] The positive electrode material particles were processed by ion milling to form the cross section of the positive electrode material particles. The acceleration voltage was 6KV, the discharge voltage was 1.5KV, and the air flow size was 0.1cm 3 / min, processing time is 50min.

[0199] A field emission scanning electron microscope (Hitachi S4800) was used to quickly obtain the cross-sectional SEM images of the cathode material particles. Under a field of view of 5k, the fields of view in different areas were randomly selected to count the number of the first type of particles and the proportion of the number of the second type of particles to the total number of cathode material particles.

[0200] Test of the area ratio of the pore structure: A scanning electron microscope (Hitachi S4800) was used to characterize the SEM image of the cross-section of the secondary particles of the positive electrode material (1.0kV 5.0mm, magnification of 5k). The area of ​​the cross-section of the secondary particles was taken as 100%, and the total area occupied by the secondary particles and the area occupied by the pore structure were calculated by the pixel method. The area ratio of the pore structure in the secondary particles was calculated. When the area ratio is less than 0.5%, the secondary particles are second-type particles. When the area ratio is between 0.5% and 30%, the secondary particles are first-type particles. The average value of the area ratio of the pore structure of the first-type particles is further calculated as the area ratio of the pore structure in the first-type particles. It should be noted that the pore structure in this application refers to a pore structure with a maximum length and width of more than 200nm in the cross-section SEM image. Please refer to Figure 3 In the cross-sectional SEM image of the first type of particles, in the circumscribed circle of the outline of a single first type of particle, the area within a radius of 2 μm radially outward from the center of the circumscribed circle is the core area, and the area other than the core area is the surface area.

[0201] Test of the maximum distance between the edges of the pore structure: In the SEM image of the secondary particle cross-section, randomly select 10 first-class particles, and use a caliper to measure the distance between any two adjacent edges of the pore structure. The maximum value of the 10 measurement results is the maximum distance between the edges of the pore structure. In the present application, the distance between the edges of two adjacent pore structures refers to the distance between the edges of two adjacent pores in two adjacent pore structures. It should be noted that in the present application, the two pore edges with the smallest distance between two adjacent pore structures are defined as two adjacent pore edges, and the two pore edges with the largest distance are defined as two pore edges far away from each other.

[0202] (3) Particle size test:

[0203] The particle size distribution of the positive electrode material particles was obtained by using the laser diffraction light intensity distribution of the British Malvern Mastersizer 3000 model laser particle size analyzer. The volume-based cumulative particle size distribution of the particle size distribution determination was measured by the laser diffraction method, D 10It indicates the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D 50 Indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D 90 It indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.

[0204] Volume particle size distribution width of positive electrode material = (D 90 -D 10 ) / D 50 .

[0205] (4) Compaction density test of positive electrode materials:

[0206] The compaction density ρ2 of the powder was tested using a compaction density meter with a pressure of 6t for 30s.

[0207] (5) XRD test analysis of positive electrode materials:

[0208] The XRD diffractometer was used to test in the range of 10°-70° at 1° / min and a step size of 0.005°; the tested XRD image was then subjected to Rietveld refinement using GASA software, with the refinement standard being RWP < 3%; after refinement, the unit cell volume, unit cell parameters c, a and cation mixing coefficients can be obtained in the unit cell parameter interface of the GSAS software.

[0209] (6) Lithium ion m in the positive electrode material Li内 and m Li外 The test method:

[0210] The positive electrode material was sectioned by an ion mill, and then the mass content of the metal Li element in the core area of ​​the positive electrode material was measured by an X-ray photoelectron spectrometer (Thermo Scientific K-Alpha). Li内, Test the mass content of the metal Li element in the surface area of ​​the positive electrode material m Li外 The surface region is the region within a radius of 2 μm from the center of the particle in the cross-sectional SEM image of the first type of particles, and the surface region is the surface region excluding the core region.

[0211] (7) Electrochemical performance evaluation using button half-cell:

[0212] After the positive electrode material is mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, NMP (N-methylpyrrolidone) is added to make a uniform slurry, the slurry is evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it is rolled at a pressure of 10Mpa and cut into a circular pole piece with a diameter of 14mm. The negative electrode uses a Li metal sheet with a diameter of 14mm. The lithium-ion battery is assembled according to the CR2025 button battery in industry. The diaphragm is a Cellgard diaphragm, and the electrolyte uses an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte are assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5ppm.

[0213] Capacity test system: The electric performance test was conducted using the Blue Electric test system (charge and discharge voltage was 3.0-4.3V, temperature was 25°C), 0.1C charging, 0.1C discharging, the first week coulombic efficiency was defined as the discharge capacity / charge capacity at 0.1C. The constant voltage cut-off current was 0.005C, and the 0.1C discharge capacity was calculated to be mAh / g.

[0214] The electrical performance test was carried out using a blue power test system (charge and discharge voltage was 3.0-4.3V, temperature condition was 25°C), 5C charging, 1C discharging, constant voltage cut-off current was 0.1C, and the 5C charging gram capacity mAh / g was calculated.

[0215] Cycle test system: 25℃, charge and discharge voltage of 3.0~4.3V, charge and discharge cycle of 0.5C / 1C for 50 cycles, the final capacity retention rate after 50 cycles is the cycle performance. The test results are detailed in Table 1 and Table 2.

[0216] Table 1 Physical and chemical properties of positive electrode materials prepared in comparative examples and examples

[0217]

[0218] Table 2 Electrochemical performance test of positive electrode materials

[0219]

[0220] According to the test data of Examples 1 to 12, the first type of particles in the positive electrode material account for 30% to 50% of all the particles, and the second type of particles account for 50% to 70% of all the particles. The two types of particles are matched with each other. The first type of particles with an appropriate number and proportion can alleviate the expansion stress generated during the lithium deintercalation process of the lattice due to the presence of the pore structure, and are beneficial to the release of the expansion stress in the lattice during the charging and discharging process (especially the fast charging process). With an appropriate amount of the second type of particles, the overall structural stability of the positive electrode material can be improved. The positive electrode material has high capacity and excellent cycle stability, and can meet the fast charging performance.

[0221] According to the test data of Example 1 and Comparative Example 1, it can be known that in the preparation process of Comparative Example 1, a uniform stirring rate is used for the coprecipitation reaction, resulting in the structure inside the precursor being close to the structure of the surface layer, and the precursor has no porous structure inside. In addition, no staged sintering process is used in the first sintering process, and the sintering temperature is 850°C, resulting in some small pore structures in the inner core and surface of the sintered product. The length and width of these small pore structures are both less than 100nm. These small pore structures will also increase the side reactions between the positive electrode material and the electrolyte, resulting in a decrease in the first coulombic efficiency of the positive electrode material, and the number of the first type of particles in all the particles is 0. During the charge and discharge process of the positive electrode material, the expansion stress generated when lithium is embedded in the lattice is difficult to be fully released, resulting in cracks in the secondary particles. Some secondary particles rupture during the cycle, resulting in a decrease in the cycle capacity retention rate.

[0222] According to the test data of Example 1 and Comparative Example 2, during the first sintering process, the heating rate of Comparative Example 2 is slow, and the temperature of the second heating stage of the first sintering treatment is low, resulting in a decrease in the temperature difference between the inner and outer layers of the precursor, a close growth rate of the primary particles, a more dispersed distribution of the pore structure in the cross-section of the secondary particles, an increase in the distance between the edges, a significant decrease in the proportion of the first type of particles, a growth distance of lithium ions inside the positive electrode material particles, a decrease in the transmission efficiency of lithium ions, and a decrease in the cycle capacity retention rate of the positive electrode material.

[0223] According to the test data of Example 1 and Comparative Example 3, in the preparation process of Comparative Example 3, the difference in stirring rates between the first and second stages of the co-precipitation reaction increases, resulting in the internal structure of the precursor being too loose. During the first sintering process, the heating rate is too fast, and the temperature in the second heating stage of the first sintering treatment is relatively high, resulting in an increase in the temperature difference between the inner and outer layers of the precursor, an increase in the pore structure inside the secondary particles, an increase in the proportion of the first type of particles, a decrease in the structural stability of the positive electrode material, an aggravation of the particle breakage phenomenon during the electrode sheet rolling process, a decrease in the capacity and first coulombic efficiency of the positive electrode material, and a decrease in the cycle capacity retention rate.

[0224] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical scope of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material includes first type particles and second type particles; In the cross-sectional SEM image of the positive electrode material, the area of ​​the pore structure within the first type of particles accounts for 0.5% to 30%; the area of ​​the pore structure within the second type of particles accounts for <0.5%; based on the total number of particles in the cross-sectional SEM image of the positive electrode material, the number of the first type of particles accounts for 50% to 70%.

2. The positive electrode material according to claim 1, characterized in that In the cross-sectional SEM image of the first type of particles, the first type of particles include a core region and a surface region, and in a circumscribed circle of the outline of a single first type of particle, a region within a radius of 2 μm radially outward from the center of the circumscribed circle is the core region, and a region other than the core region is the surface region; The number of the pore structures distributed in the core region accounts for R, and R≥70%.

3. The positive electrode material according to claim 2, characterized in that The mass content of lithium ions in the core region is m Li内 The mass content of lithium ions in the surface area is m Li外 , 0.55≤m Li内 / m Li外 ≤0.

85.

4. The positive electrode material according to claim 2, characterized in that In the cross-sectional SEM image of the first type of particles, the maximum distance between the edges of any two adjacent pore structures is ≤2.5 μm.

5. The positive electrode material according to any one of claims 1 to 4, characterized in that The chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.30, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and M includes at least one of Mo, Ti, Zr, Sb, Y, W, Al, Sr, Ba, Ca and B.

6. The positive electrode material according to any one of claims 1 to 4, characterized in that The volume distribution particle size D50 of the positive electrode material is 7 μm to 12 μm.

7. The positive electrode material according to any one of claims 1 to 4, characterized in that The compaction density of the positive electrode material is 2.8 g / cm 3 ~3.5g / cm 3 .

8. The positive electrode material according to any one of claims 1 to 4, characterized in that The lithium-nickel mixing rate of the positive electrode material is 2% to 6%.

9. The positive electrode material according to any one of claims 1 to 4, characterized in that The positive electrode material is subjected to XRD measurement using Cu-Kα rays, and the positive electrode material satisfies at least one of the following characteristics: (1) Unit cell volume of the positive electrode material (2) the unit cell parameter c of the c-axis of the positive electrode material, (3) the unit cell parameter a of the a-axis of the positive electrode material, (4) The positive electrode material unit cell parameter ratio c / a>4.

94.

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.

Citation Information

Cited By

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN120581576A

  • Positive electrode material and battery

    WO2026195080A1